2022
DOI: 10.1007/s11606-022-07500-w
|View full text |Cite
|
Sign up to set email alerts
|

Medical Schools as Racialized Organizations: How Race-Neutral Structures Sustain Racial Inequality in Medical Education—a Narrative Review

Abstract: In 2021, The American Association of Medical Colleges released a framework addressing structural racism in academic medicine, following the significant, nationwide Movement for Black Lives. The first step of this framework is to "begin self-reflection and educating ourselves." Indeed, ample evidence shows that medical schools have a long history of racially exclusionary practices. Drawing on racialized organizations theory from the field of sociology, we compile and examine scholarship on the role of race and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 75 publications
0
40
0
Order By: Relevance
“…Indeed, studies have reported a more substantial application-matriculation gap among URM trainees applying to surgical specialties than among Asian and White trainees. 3 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have reported a more substantial application-matriculation gap among URM trainees applying to surgical specialties than among Asian and White trainees. 3 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Black medical students apply to multiple specialties, either out of greater uncertainty or concerns about successfully matriculating in their preferred specialty. Indeed, studies have reported a more substantial application-matriculation gap among URM trainees applying to surgical specialties than among Asian and White trainees …”
Section: Discussionmentioning
confidence: 99%
“…There were 4 domains of variables hypothesized a priori as barriers (Table 1). The first is parental educational level, which we examined as a proxy for wealth . For this proxy, we used the AAMC variable of not having a parent with a bachelor’s degree .…”
Section: Methodsmentioning
confidence: 99%
“…As Nguemeni Tiako et al and others have written, this structural racism leads to several barriers for groups underrepresented in medicine, including differences in parental educational level and resources and differences in the networks and informal knowledge required to, among other things, secure clinical shadowing and other extracurricular educational opportunities valued in the medical school application process. Interpersonal discrimination creates yet another barrier whose influence can occur anywhere along the process . These barriers may help explain why groups underrepresented in medicine are more likely to declare in high school their intentions of becoming a physician than they are to apply to or matriculate at medical school .…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence implicates structural racism as the foundational contributor to disparities in family wealth and educational opportunities that limit the resources needed for individuals to successfully apply and matriculate into medical school . Such factors upstream from the application and matriculation process must be addressed to advance parity in medical school access.…”
mentioning
confidence: 99%